Sexualité préconjugale, souillure et reconstruction de soi. Les adolescentes au prisme d’une politique du corps féminin en Tunisie - Meryem Sellami (L’Année du Maghreb)
Through the course of ethnographic research started over a decade ago about women’ bodies in Tunisia, this article suggests that the way to realize the imperative to control these women’ sexuality is found at the heart of a body politics that targets exclusively the governance of feminine gender. This politics articulates in particular the perpetuation of virginal norm for women. A social norm, which may be an object of critique and circumvention by girls and boys nowadays in Tunisia, remains symbolically effective and maintains a “Differential valence of sexes” (Héritier, 1996). Feminine prenuptial sexuality, even if it is tolerated in the interstices of the social, remains highly a source of guilt and shame for girls. Maintaining guilt constitutes the central basis of sexual hierarchies as well as a source of eventual suffering for young women. The field work conducted with teenage girls that cut their bodies or forces themselves to throw up supports this hypothesis and reflects singular ways to address gender inequalities related to sexuality, notably through the recourse to the sacred.